2012
DOI: 10.1016/j.jmb.2012.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Proteins from Sequence Statistics: The Interplay of Conservation and Correlation in Triosephosphate Isomerase Stability

Abstract: Understanding the determinants of protein stability remains one of protein science's greatest challenges. There are still no computational solutions that calculate the stability effects of even point mutations with sufficient reliability for practical use. Amino acid substitutions rarely increase the stability of native proteins; hence, large libraries and high-throughput screens or selections are needed to stabilize proteins using directed evolution. Consensus mutations have proven effective for increasing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 52 publications
1
88
1
Order By: Relevance
“…To investigate how our results compare with the natural sequence record, we used a large GH1 multiple sequence alignment to calculate a relative entropy sequence conservation score (22,23). Bgl3's mutational tolerance shows a strong correspondence with the observed GH1 sequence conservation.…”
Section: Significancementioning
confidence: 99%
“…To investigate how our results compare with the natural sequence record, we used a large GH1 multiple sequence alignment to calculate a relative entropy sequence conservation score (22,23). Bgl3's mutational tolerance shows a strong correspondence with the observed GH1 sequence conservation.…”
Section: Significancementioning
confidence: 99%
“…These observations also suggested an algorithm to improve consensus design, by making consensus mutations at more-conserved positions and eliminating mutations at highly correlated positions [63,64]. The result in yeast TIM was a 90+% success rate in identifying stabilizing mutations, and large numbers of the mutations could be productively aggregated.…”
Section: Effects Of Sequence Correlationmentioning
confidence: 99%
“…Consensus residues do not always improve protein stability. Sullivan et al (33) reported that removal of consensus mutations at positions for which their effect is statistically coupled to a residue(s) at another site(s) tends to improve stability. Therefore, the stability of ConsNDK might be increased if its sequence was optimized according to the finding of Sullivan et al…”
Section: Robustness Of the Tree Topologies Used To Infer The Ancestralmentioning
confidence: 99%